Method of acoustic assessment of machinery based on global acoustic quality index - PLEBAN, Dariusz (Archives of Acoustics, 2010)
For the use of acoustic assessment of machinery, a global index of acoustic quality has been developed. Acoustic quality index is considered as a product of the following partial indices: sound power index, index of distance between the workstation and the machine, radiation directivity index, impulse and impact noise index and noise spectrum index. Each partial index always assumes positive value. If the value of global index does not exceed 1, the noise of the assessed machine will not exceed the admissible value of A-weighted sound pressure level at the workstation.Experimental tests were carried out in order to determine the values of global indices for a group of engine-generators, with the use of inversion method allowing for the determination of sound power level. The correctness of the determined values of indices was confirmed by the results of A-weighted sound pressure level measurements, at the hypothetically assumed workstations in simulated in situ conditions.